Characterization of spatial heterogeneity in underwater soundscapes at the river segment scale - Diego Tonolla; Mark S. Lorang; Kurt Heutschi; Chris C. Gotschalk; Klement Tockner (Limnology and Oceanography, 2011)
The patterns of underwater acoustic signals, called soundscapes, were characterized at the river segment scale. A hydrophone was mounted onto the frame of an inflatable multihull raft and held just below the water's surface while floating for 5–24 km to continuously record acoustic signals along the longitudinal axis of the main channel (thalweg) of five hydro‐geomorphologically different river segments in Italy, Switzerland, and the United States of America. The river segments could be clearly distinguished based on sound pressure level (SPL), sound variability, and the spatial organization of the acoustic signal (10 octave bands: 0.0315–16 kHz). The spatial soundscape diversity between river segments was most likely related to the organization of turbulence along the segment length (distance between rapids) and to sound source (hydraulic turbulence or local sediment transport). Hydraulically and morphologically heterogeneous segments revealed more complex soundscapes than more homogeneous ones. Higher flow levels resulted in higher SPLs over most frequency bands. The acoustic variability of single octave bands increased from base to intermediate flow, while it decreased from intermediate to bankfull flow. The pulsating sound produced by breaking and reforming turbulent waves on flow obstacles was associated with SPL peaks and high acoustic variability in midrange frequency bands (0.063–0.5 kHz), whereas high‐frequency SPLs (1–16 kHz) were related to particle collisions during streambed sediment transport. Underwater soundscapes provide an independent measure to quantify habitat heterogeneity and spatial habitat organization that can be applied to river corridors at the segment scale.